Hookworm Infection among Pregnant Women at First Antenatal Visit in Lira, Uganda: A Cross-Sectional Study - Apili, Felister; Ochaya, Stephen; Osingada, Charles Peter; Mbalinda, Scovia Nalugo; Mukunya, David; Ndeezi, Grace; Tumwine, James K. (International Journal of Reproductive Medicine, 2020)
Background. Hookworm infection in expectant mothers has adverse health effects on both the mothers and their unborn babies. Foetal effects are known to include intrauterine growth retardation and physical and mental growth retardation, while the mothers may develop anemia which could potentially result in death. Unfortunately, little is known about factors that may predispose a pregnant woman to infection by hookworm. In this study, we strived to determine not only the prevalence of hookworm infection among pregnant women attending their first antenatal visit during the current pregnancy in a local health center in northern Uganda but also factors that might predispose them to hookworm infection. Method. This cross-sectional study was conducted among 346 pregnant women from Ogur Health Center IV located in Lira district, northern Uganda. Stool samples were collected from each study participant and analyzed for hookworms. The independent variables listed in this study (participant’s sociodemographic characteristics, preconception care, and sanitation factors) were obtained using a structured questionnaire. Data analysis, including calculation of adjusted ratios, was performed using STATA software (version 14). Results. Prevalence of hookworm infection among pregnant women who attended their first antenatal visit at Ogur Health Center IV was 11% (n=38). After controlling for confounders, factors found to be significantly associated with this infection among pregnant women here were gardening barefooted (adjusted odds ratio (AOR), 3.4; 95% confidence interval (CI), 1.6 to 7.5; P<0.001) and fetching unsafe water shared with animals for domestic uses (AOR, 2.8; 95% CI, 1.3 to 6.2; P value of 0.002). Conclusion. Hookworm infection among pregnant women at Ogur Health Center IV in Lira district, at 11%, is a public health concern and significantly associated with barefoot gardening and fetching water from unsafe sources shared with animals. We, therefore, recommend that special emphasis during routine prenatal health education be placed on the use of protective footwear during farming and fetching water for domestic use from protected safe sources. Author Summary. Hookworm infection is a parasitic condition that more often goes unnoticed, yet it presents immense detrimental effects, especially to pregnant women and their unborn children. It is a chronic disease with accruing effects of blood depletion resulting in anemia. Anemia is, by far, one of the major causes of maternal morbidity and mortality in Uganda. Pregnant women are more prone to hookworm infection by virtue of their compromised immunity, secondary to the physiological process of pregnancy. We demonstrated here that hookworm infection still exists among pregnant women in Uganda. We also showed that gardening barefooted and fetching water for domestic uses from unsafe sources shared with animals were major factors associated with this helminthic infection. This study provides evidence necessary to influence decision making on prevention of hookworm infection in the study area.